Eosinophilic Pleural Effusion: A Rare Complication of Extracorporeal Shock Wave Lithotripsy - Maral Mokhtari; Perikala Vijayananda Kumar; Mohammad-Ali Ghayumi (Case Reports in Medicine)
Background. Extracorporeal shock wave lithotripsy has been widely used to treat renal stones. The procedure is relatively safe with minor complications. Case. The patient is a 32-year-old man who presented with left sided pleural effusion after extracorporeal shock wave lithotripsy. Results. The pleural effusion study revealed an exudative fluid rich in eosinophils (30%). So, the diagnosis of eosinophilic pleural effusion as a complication of lithotripsy was made. Conclusion. Extracorporeal shock wave lithotripsy should be regarded as an etiology of unexplained eosinophilic pleural effusion after this procedure.